Assignment peace in the name of the motherland - Mendis, L. M. H. (Nugegoda : L.M.H. Mendis, 2002)
On the various army operations other than war and counterinsurgency in Sri Lanka between 1996-1999, against Liberation Tigers of Tamil Eelam.
Keywords: Battles -- Sri Lanka; Sri Lanka -- History, Military; Sri Lanka -- History -- 1948-